Invisible Gold and Other Impurity Elements in Pyrite and Arsenopyrite of Disseminated Ores of the Kyuchus Deposit (Sakha Republic (Yakutia)) - Sidorova N.V.; Volkov A.V.; Kovalchuk E.V.; Minervina E.A.; Levitskaya L.A. (My University, 2022)
For the first time, EPMA and LA-ICP-MS data were obtained for the Kyuchus Au–As–Sb–Hg deposit on variations in the grades and zonal distribution of gold and other impurity elements in gold-bearing sulfides of disseminated ores. Two types of zoning have been found in pyrite: (1) zoning with the central zone depleted in impurities bearing As (1.5–1.9 wt %) and Au (~up to 5 ppm), an impurity-enriched intermediate zone (As up to 5.4 wt %), and an outer rim with contents of As of about 3 wt % and Au (LA-ICP-MS 20–30 ppm; EPMA 0.03 wt %); (2) zoning with central zones enriched in arsenic (up to 7 wt %) and markedly arsenic-depleted (3.6–5.8 wt %) rims with Au content up to 310 ppm (EPMA). Arsenopyrite also has a zoned structure with a central zone enriched in Sb; the amount of As and Au increases towards the edges of crystals. Compared to pyrite, arsenopyrite is characterized by higher Co, Ni, Ag, Sb, Au, Hg contents and lower Cu contents. According to the EPMA data, the Au content in arsenopyrite reaches 0.2 wt %; in pyrite, 0.03 wt %. In arsenopyrite, the maximum gold concentrations are confined to the edges of the crystals. In pyrite, the maximum Au concentrations are in marginal rims and cribrose-cellular regions of grains. For both sulfides, no significant correlation was found between gold or other elements.
Keywords: Northern Yakutia; Kyuchus deposit; pyrite; arsenopyrite; invisible gold; EPMA; LA-ICP-MS